2024
DOI: 10.2174/0109298673262124231102042914
|View full text |Cite
|
Sign up to set email alerts
|

The Link between miRNAs and PCKS9 in Atherosclerosis

Mirjana T. Macvanin,
Zoran M. Gluvic,
Aleksandra N. Klisic
et al.

Abstract: Cardiovascular disease (CDV) represents the major cause of death globally. Atherosclerosis, as the primary cause of CVD, is a chronic immune-inflammatory disorder with complex multifactorial pathophysiology encompassing oxidative stress, enhanced immune-inflammatory cascade, endothelial dysfunction, and thrombosis. An initiating event in atherosclerosis is the subendothelial accumulation of low-density lipoprotein (LDL), followed by the localization of macrophages to fatty deposits on blood vessel walls, formi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 297 publications
0
1
0
Order By: Relevance
“…Previous studies have identified oxidative stress as a risk factor for the development of some NCDs, such as CVD, DM, and cancer. Atherosclerosis caused by oxidative stress and chronic inflammatory cascade reaction is the most important etiology of CVD, as reported by Macvanin et al ( 4 ). Another study indicated that one of the reasons for insulin resistance may be the destruction of pancreatic β-cells caused by oxidative stress.…”
Section: Introductionmentioning
confidence: 85%
“…Previous studies have identified oxidative stress as a risk factor for the development of some NCDs, such as CVD, DM, and cancer. Atherosclerosis caused by oxidative stress and chronic inflammatory cascade reaction is the most important etiology of CVD, as reported by Macvanin et al ( 4 ). Another study indicated that one of the reasons for insulin resistance may be the destruction of pancreatic β-cells caused by oxidative stress.…”
Section: Introductionmentioning
confidence: 85%